CULTURAL LINGUISTIC STUDIES OF THE CONCEPTS: FRAME ANALYSIS - Mukhammadiyarov Aydos Joldasbaevich; Tajiyeva Aliya Utebaevna (KONFERENSIYALAR, 2025)
Annotation.    The  given  article  reveals  that  cultural  linguistic  peculiarities  are  expressed based  on  the  concept  especially  in  the  field  of  translation  studies.  The  main  method  to  analyze translated Byron’s poem in  Karakalpak is  to  find out  basic lexical frames which can help  us to conceptualize human soul universally. Doing the frame (framing) analysis by which Ervin Goffman started to use in his book, we identified that the «soul» is the main concept in people connecting with love, sorrow, motherland, longing, and despair and in translations of the poems «Lines written in an album» by Byron the «soul» was shown similarly both in meaning and translating. In the end, the essential frames like traveler, a dead person, grave, remedy, bridge, darkness, can help one to embody  the  author’s  soul  and  were  classified  into  framing  subgroups,  such  as  linguistic  frame, emotional  and  spiritual  frame,  metaphorical  frame,  philosophical  frame,  structural  frame, contextual frames.